The English Translation of French Negation in Amour Film - Mukti, Gabriella Anggun Yunita; Matradewi, Ni Ketut Widhiarcani; Soethama, Putu Lirishati (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This study is entitled The English Translations of French Negation in Amour Film. This study aims to find out the distinctions between French and English negation through the types of negation sentence forms and how French negation, as the source language, is translated into English in the subtitle. The data source was taken from the Amour film. The method used in collecting data is documentation with note-taking techniques. Qualitative descriptive method is used in analyzing the data that has been collected. The theory used to identify the data is the theory of translation equivalence by Nida. Meanwhile, the negation of French and English is determined using the theories of Hawkins (2001) and Huddleston (2005). Based on the theory of translation by Nida, there are two kinds of equivalence: formal equivalence and dynamic equivalence. The results of this study showed that there were 91 data points from French negation in the Amour film; 70 were identified as formal equivalence, and 21 were identified as dynamic equivalence. Based on the two problems of the study, there were six types of French negation and four types of English negation. Keywords: Translation, French negation, English negation